Penurunan Pertumbuhan Tajuk Kedelai [Glycine max (L.) Merr.] Akibat Cekaman Ganda Interferensi Teki (Cyperus rotundus L.) dan Kekeringan - Darmanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Plants under stress conditions will decrease the variety of physiological processes speed, so the growth and production did not reach the genotypes potential. Weeds interference and drought stress that occurred simultaneously is one of obstacle in improving the soybean [Glycine max (L.) Merr.] production. Purple nutsedge (Cyperus rotundus L.) is the important weeds in soybean, invasive and difficult to eradicate. This research uses experimental method completely randomized design of two factors such as the level of water supply and the level of purple nutsedge interference. Each treatment unit, with five replications. The aim of this research to determine multiple stress of purple nutsedge interference and drought stress effect to the decrease of soybean shoot growth. The results showed that combination of three or six purple nutsedge interference with mild or severe drought stress causes a decrease of fresh weight, dry weight and length soybean shoot. The more weight the greater levels of stress decrease. The smallest decrease occurred in the shoot length parameter and successive increases in dry weight and wet weigh. Keywords : multiple stress, Cyperus rotundus L., Glycine max (L.) Merr., growth, shoot